Understanding and Targeting the Colon Cancer Pathogenesis: A Molecular Perspective - Khan, Imran (Brazilian Journal of Pharmaceutical Sciences, 2022)
Abstract Colorectal cancer (CRC) one of the leading cause of cancer-related deaths worldwide. With the presently available knowledge on CRC, it is understood that the underlying is a complex process. The complexity of CRC lies in aberrant activation of several cellular signaling pathways that lead to activation and progression of CRC. In this context, recent studies have pointed towards the role of developmental pathways like; hedgehog (HH), wingless-related integration site (WNT/β-catenin) and Notch pathways that play a crucial role in maintenance and homeostasis of colon epithelium. Moreover, the deregulation of these signaling pathways has also been associated with the pathogenesis of CRC. Therefore, in the search for better therapeutic options, these pathways have emerged as potential targets. The present review attempts to highlight the role of HH, WNT/β-catenin and Notch pathways in colon carcinogenesis.